Development of PV output power indicator using PIC for battery charging system / Farah Fatin Zulkifli - Zulkifli, Farah Fatin (2011)
Development of Photovoltaic (PV) output power indicator using Programmable Interface Controller (PIC) for battery charging system is one of the improvements in the photovoltaic monitoring system. This project was inspired by the problem of measuring power manually which need quite some time to get the output. By this project, output power of battery charger would be displayed on the Liquid Crystal Display (LCD). PIC is use to program the LCD. First of all, student have to understand basic concepts of each elements involved in photovoltaic system such as PV module, charge controller and battery charger. Current sensor ACS 712 is use to detect current while voltage divider is use to step down the voltage of battery charger. Student need to research on how to match output of sensor as an input of PIC. Then, program was designed to indicate power by using C programming.